FAKTOR PENYEBAB KECELAKAAN LALU LINTAS DAN PERILAKU BERKENDARA PADA SISWA SEKOLAH MENENGAH ATAS DI PASIR PENGARAIAN RIAU - Khairul Fahmi (Jurnal Ilmiah Cano Ekonomos, 2021)
Traffic accidents at a young age often occur because of the low perception of the risk of danger on the highway. Teenagers were a group of motorcycle users who often ignore traffic rules. The purpose of this study was to provide an overview of the causes of traffic accidents and traffic safety behavior while driving to senior high school students in Pasir Pengaraian. This research was aquantitative research with a cross-sectional design. The research was conducted in 3 senior high schools in Pasir Pengaraian. The number of respondents as many as 368 students were taken using purposive sampling. The respondents of this study were students who rode motorbikes to school. Data was collected through questionnaires sent via google form to each individual. Data analysis usedunivariate and bivariate analysis using chi square with 0.05%. The results showed that the accident rate was 27.4%, the reason for using motorbikes to go to school was because there was no one to drive 21.5%, 44.8% distance from school and 94.8% of respondents did not have a driver's license. As for the relationship between the incidence of accidents and behavior while driving, there was arelationship between the incidence of accidents and the behavior of violating the yellow light p = 0.017, calling hp p = 0.007, sending sms p = 0.002, driving at high speed p = 0.01 and driving more than 2 people p=0.019, driving while listening to music on cellphone p=0.011 and driving without wearing a helmet p=0.016. Other driving behaviors such as smoking while driving, violating road markings and violating traffic signs have no relationship with the incidence of accidents.